O40-4 Lung function decline and copd prevalence in relation to occupational exposures in a prospective cohort study: the ecrhs III. (1st September 2016) - Lytras, Theodore; Carsin, Anne-Elie; Kromhout, Hans; Vermeulen, Roel; Antó, Josep Maria; Bakke, Per; Benke, Geza; Blanc, Paul; Dorado, Sandra; Hellgren, Johan; Holm, Mathias; Jarvis, Deborah; et al.
Abstract : Introduction: Few prospective population-based studies have demonstrated a relationship between occupational exposures and the rate of lung function decline. We examined the effect of occupational exposures on lung function decline (FEV1 and FVC) and COPD prevalence in the ECRHS, a multicentre cohort study that has completed its second follow-up after a mean of 19 years. Methods: We used repeated questionnaire and pre-bronchodilator spirometric data from 9175 ECRHS participants in 29 study centres who completed the first follow-up; 4549 (50%) of them completed the second follow-up. COPD was defined using a lower limit of normal criterion for FEV1/FVC. Occupational exposures were assessed from job histories up to the first follow-up using the ALOHA Job-Exposure Matrix. Decline in FEV1 and FVC was analysed using mixed-effects linear models, and change in COPD prevalence using marginal (GEE) logistic regression. All models were adjusted for age, gender, height, BMI, smoking status, passive smoking, current asthma, socioeconomic status, and early-life disadvantage score. To account for differential loss to follow-up and item non-response we used multiple imputation with chained equations (100 imputed datasets). Results: In women, exposure to low levels of dusts, gases or fumes resulted in accelerated declines in FEV1 (−1.4 ml/yr; 95% CI: −2.8 to 0.0) and FVC (−1.7 ml/yr; −3.4 to −0.1); FEV1 decline was higher in female smokers (−3.1 ml/yr; −4.8 to −1.3). In men, the same exposures had a statistically significant effect only in smokers, with accelerated declines in FEV1 (−3.2 ml/yr; −5.1 to −1.2) and the FEV1/FVC ratio (−0.6%/10 years; −1.1% to −0.2%), as well as an increased prevalence of COPD (OR = 1.21; 1.03–1.43). Higher exposures produced similar effects, in both genders. Conclusions: Occupational exposures appear to affect lung function decline and COPD prevalence, and the magnitude of this effect depends on gender and smoking status.